Analisis Strategi Persuasif pada Tindak Tutur Ria Ricis dalam Channel Youtube Ricis Official - Sa'diyah, Rizqotus (Universitas Nusantara PGRI Kediri, 2021)
This study aims to describe the persuasive strategies of direct speech acts and indirect speech acts of ria ricis in the ricis official youtube channel and to describe the persuasive strategies of ria ricis in the ricis official youtube channel when viewed from direct speech acts and indirect speech acts. The research method used is descriptive qualitative method. The data collection technique used the note-taking technique. Data analysis techniques are carried out by collecting data, reducing data, presenting data, and drawing conclusions. Based on the results of this study, it shows that (a) the direct speech act strategy of ria ricis on the ricis official youtube channel consists of three categories, namely speech act strategies in the form of news sentences (declarative), interrogative sentences (interrogative). And imperative sentences (imperative). (b) the indirect speech act strategy consists of two categories, namely the indirect speech act strategy in the form of news sentences and interrogative sentences. (c) the persuasive strategy when viewed from direct speech acts and indirect speech acts has a very different number where persuasive strategies that use direct speech acts are more widely used by ria ricis than persuasive strategies that use speech acts indirect.